Pengaruh Gaya Kepemimpinan dan Komunikasi terhadap Kinerja Karyawan dengan Kepuasan Kerja dan Motivasi sebagai Variabel Intervening pada PT KB Finansial Multi Finance Cabang Bogor - Herman Susilo; Rian Marciana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of leadership and communication style on employee performance with job satisfaction and motivation as intervening variables at PT KB Finansial Multi Finance Bogor Branch. This study uses a quantitative approach with data collection techniques through the distribution of questionnaires to 100 respondents. Data analysis was carried out using SmartPLS 3.0. The results of the study show that leadership and communication styles have a positive and significant effect on employee performance. Leadership style and communication also have a positive and significant effect on job satisfaction, while communication has a positive and significant effect on motivation, but leadership style does not have a significant effect on motivation. In addition, job satisfaction and motivation have no significant effect on employee performance. The results of the indirect influence test showed that job satisfaction and motivation were unable to mediate the influence of leadership style and communication on employee performance. Thus, communication is the most dominant variable in improving employee performance at PT KB Finansial Multi Finance Bogor Branch.